Precocious Pubic Hair Development: A Team-Based Learning Review of the Hypothalamic-Pituitary-Adrenal Axis and Puberty - Emily Walvoord; Julie Vannerson; Simon Rhodes (Association of American Medical Colleges, 2010)
Abstract Introduction This team-based learning (TBL) case on precocious pubic hair development was written in a joint effort of a clinician and a basic scientist to provide students with a clinical vignette to further explore endocrinology physiology. Methods In the application portion of this TBL, a 2-year-old female was referred by her primary care doctor to a pediatric endocrinologist for an evaluation of early pubic hair. The application is done so the events unfold over time. There are eight multiple-choice questions students work on as a group and then are debriefed as a large group, in addition to two short-answer questions that ask the students to think of possible implications of the findings throughout the case. Results Students were very positive and appreciated how the case helped to correlate their study of adrenal glands and endocrinology in physiology with a real-patient scenario. Discussion The educational goals include an understanding of the basic anatomy and histology of a human adrenal gland and understanding the features of diseases resulting from excess or insufficiency of glucocorticoid hormones. In this case, a pediatric endocrinologist was able to share her methods of dealing with highly emotional and complex communications with the parents of the child.